Peningkatan Hasil Belajar Dengan Model PAKEM Pada Bahasa Indonesia Dalam Menyimpulkan Cerita Anak Pada Siswa Kelas VA SDN Cikidangbayang Mande - Renny Nur Afriyani; Iis Ristiani (Jurnal Pendidikan, Bahasa dan Budaya, 2023)
This study aims to describe learning outcomes through the application of the PAKEM learning model. The research subjects were students of class Va SD Negeri Cikidangbayabang Kec. Mande. The improvement of learning outcomes was reviewed from four categories, namely absorption, learning effectiveness, student learning completeness both individual completeness and classical completeness and completeness of learning outcomes. The instruments used for data collection were reading tests and written tests in the form of LKS which were carried out after the learning process. The results showed that the percentage of student completeness increased from 33.33% to 73.33% categorized as good, the effectiveness of learning was categorized as very effective. While the completeness of student learning outcomes was declared complete. Based on the results of the study, it can be concluded that the application of the PAKEM learning model can improve learning outcomes in the material of Summarizing the contents of children's stories in several sentences in class Va students of SD Negeri Cikidangbayabang Kec. Mande.